Gasdermin E benefits CD8+T cell mediated anti-immunity through mitochondrial damage to activate cGAS-STING-interferonβ axis in colorectal cancer - Bixian Luo; Shun Zhang; Xinbo Yu; Dan Tan; Ying Wang; Mingliang Wang (BMC, 2024)
Abstract Background Pyroptosis belongs to a unique type of programmed cell death among which GSDME is reported to exert anti-tumor immunity. However, the underlying mechanisms of how to boost tumor-infiltrating lymphocytes and whether it could benefit the efficacy of ICIs are still unknown. Methods CRC samples were used to analyze its relationship with CD8+T cells. GSDME in mouse CRC cell lines CT26/MC38 was overexpressed. The infiltration of CD8+T cells in grafted tumors was determined by multiplex flow cytometric analysis and immunohistochemistry. Transcriptomic analysis was performed in cell lines to define key signatures related to its overexpression. The mechanism of how mtDNA was released by GSDME-induced mitochondrial damage and activated cGAS-STING pathway was observed. Whether GSDME benefited ICIs and the relationships with the genotypes of CRC patients were investigated. Results It had favorable prognostic value in CRC and was positively associated with increased number and functionality of CD8+T cells both in human samples and animal models. This was due to mitochondrial damage and activation of cGAS-STING-IFNβ pathway for the recruitment of CD8+T cells. Mechanically, GSDME overexpression enhanced N-GSDME level, leading to the mitochondrial damage and mtDNA was released into cytosol. Finally, GSDME benefited with ICIs and exhibited positive relationships with MSI in CRC patients. Conclusion We presented the mechanism of GSDME in anti-tumor immunity through activating cGAS-STING-IFNβ axis mediated by mitochondrial damage, leading to more infiltration of CD8+T cells with synergistic efficacy with ICIs.